Development and expert-evaluation of FORENSICA-android application for estimating post-mortem interval - Beta Ahlam Gizela; Idha Arfianti Wiraagni; Firdaus Firdaus; Budiatri Retno Noormaningrum; Busyra Busyra; Wendi Wiradinata; Ahnav Bil Auvaq; Nurholis Majid (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2022)
Death registration is very important and has civil and legal impact on the deceased person and their family. Validity of a death certificate is influenced by the time accuracy of death estimation. Calculation of the post-mortem interval has a central role in the estimation of the time of death, especially for death cases in the community, without prior medical observation. This study aimed to develop a smartphone application for counting the estimated time of death based on android features, to help doctors establish a more accurate time of death and provide a learning facility for doctors and medical student. This action research consisted of 4 cycles: 1) Planning, 2) Action, 3) Observation, and 4) Reflection. The final result of this study is an android application named Forensica 3rd version. This application was developed in Bahasa Indonesia. This application has a menu for recording the patient identity, instructions for post-mortem changes examination, record examination results, time of death calculation and its interpretation. This 3rd version of the application is the latest version after undergoing two revisions. The Forensica application provides an easy way for doctors and medical students to establish the time of death estimation and it is user-friendly.